Peranan Sistem Informasi Akuntansi dan Pengendalian Internal terhadap Fraud Akuntasi Berbasis Komputer - Putri Afrilia Nurrochmah; Yuyun Yuyun; Nera Marinda Machdar (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
An essential component of each scientific paper is the author's theoretical background and prior investigations. Theories of correlation between variables and events can be explained by prior study. This article's goal is to generate a hypothesis about the relationship between variables that will be investigated further. The following are the findings from this review of the literature: 1) Fraud in computerized accounting information systems is positively and significantly impacted by the role of accounting information systems. 2) Fraud using computerized accounting systems is positively and significantly impacted by internal control.